2016
DOI: 10.1155/2016/4861260
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Medial Plating of Low-Energy Lisfranc Injuries: Preliminary Experience with Five Cases

Abstract: Fracture dislocations involving the Lisfranc joint are rare; they represent only 0.2% of all the fractures. There is no consensus about the surgical management of these lesions in the medical literature. However, both anatomical reduction and tarsometatarsal stabilization are essential for a good outcome. In this clinical study, five consecutive patients with a diagnosis of Lisfranc low-energy lesion were treated with a novel surgical technique characterized by minimal osteosynthesis performed through a minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…However, their follow-up was only 19 months, on average, and the study only included 5 patients. 7 Wagner et al reported on 22 patients with low-energy injuries treated with a percutaneous technique. While their study primarily aimed to evaluate the results of early weightbearing following percutaneous fixation, their patient-reported outcomes demonstrated very good to complete satisfaction with an average AOFAS score of 94 (range, 90-100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their follow-up was only 19 months, on average, and the study only included 5 patients. 7 Wagner et al reported on 22 patients with low-energy injuries treated with a percutaneous technique. While their study primarily aimed to evaluate the results of early weightbearing following percutaneous fixation, their patient-reported outcomes demonstrated very good to complete satisfaction with an average AOFAS score of 94 (range, 90-100).…”
Section: Discussionmentioning
confidence: 99%
“…4,23 In an effort to minimize these soft tissue complications, techniques that minimize iatrogenic soft tissue trauma and dissection, such as fluoroscopically assisted percutaneous techniques, are becoming more commonplace. 5,7…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we want to mention that all the coauthors of this letter usually perform minimally invasive procedures 2,4 -6 on a regular clinical basis. Nevertheless, we would like to emphasize that these procedures must continue growing through safe steps and valid information to ensure their persistence in the future.…”
Section: Discussion: Results Discussed Seem Incongruent When Comparedmentioning
confidence: 99%
“…However, concern has been raised regarding further articular cartilage damage during the introduction of screws. [ 24 ] Currently, bridging plate fixation is more often used in internal fixation for Lisfranc injury. [ 25 , 26 ] In our study, for patients with metatarsal shaft or base fracture, screw fixation may cause implant failure.…”
Section: Discussionmentioning
confidence: 99%